2021
DOI: 10.3390/clinpract11040105
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Contraception and Massive Pulmonary Embolism in a COVID-19 Ambulatory Patient: A Case Report

Abstract: Coronavirus 19 disease (COVID-19) presents a highly variable clinical presentation and course, ranging from asymptomatic patients to rapidly progressive, fatal pneumonia. The known heterogeneous outcomes can affect both previously healthy patients and those with significant comorbidities, who develop clinical courses with possibly more multisystemic compromise. Likewise, the development of thrombotic phenomena during the acute course of the disease is associated with complications that worsen patient prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the described patient, the embolism was due to an overlap of several unfavourable circumstances, namely the girl had a history of coronavirus infection and was also on hormonal oestrogen contraceptives to treat acne vulgaris (11,12) . Significantly increased IgG antibodies, as well as hair loss, which may be one of the distant symptoms of COVID-19 disease, confirmed the past SARS-CoV-2 infection.…”
Section: Fig 2 Follow-up Ct After 2 Months Partial Restoration Of The...mentioning
confidence: 98%
See 2 more Smart Citations
“…In the described patient, the embolism was due to an overlap of several unfavourable circumstances, namely the girl had a history of coronavirus infection and was also on hormonal oestrogen contraceptives to treat acne vulgaris (11,12) . Significantly increased IgG antibodies, as well as hair loss, which may be one of the distant symptoms of COVID-19 disease, confirmed the past SARS-CoV-2 infection.…”
Section: Fig 2 Follow-up Ct After 2 Months Partial Restoration Of The...mentioning
confidence: 98%
“…Valenzuela-Vallejo et al described a case of a 45-year-old overweight (another risk factor for thrombosis) woman infected with SARS-CoV-2, a long-term user of COCs, the active ingredients of which were levonorgestrel (synthetic progestogen and also a component of single-component or combined contraceptive pills) and oestradiol (one of the three natural estrogenic hormones), who presented with symptoms of shock due to massive PE requiring thrombolysis. The authors discussed the impact of risk factors on the development of embolism and emphasised the need for reporting similar cases (11) .…”
Section: Fig 2 Follow-up Ct After 2 Months Partial Restoration Of The...mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the midwife in this determinant may increase women's desire to visit contraceptive services. Research conducted in Indonesia showed that the role of midwives can increase women's desire to visit contraceptive services and can increase the need for contraception (Valenzuela-Vallejo et al, 2021).…”
Section: Health Factormentioning
confidence: 99%